Terapi Murottal dalam Mengatasi Gangguan Pola Tidur pada Pasien Lansia - Dayuningsih Dayuningsih; Meria Woro Listyorini; Adolfina Tandilangan; Koko Wahyu Tarnoto; Rita Setianingrum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine murottal therapy in treating sleep pattern disorders in patients. This research method uses quantitative research with a quasi-experimental research design. The results of research using the Wilcoxon test showed that the P-value was 0.000. Conclusion: There is an influence on the sleep quality of older people after listening to the Murottal Al-Qur'an. The duration providing Al-Qur'an or sound therapy for 15-30 minutes can improve the quality of older people's sleep comfort and increase the relaxation effect. Keywords: Sleep Disorders, Elderly Patients, Murotal Therapy